2013
DOI: 10.2337/dc12-1288
|View full text |Cite
|
Sign up to set email alerts
|

25-Hydroxyvitamin D in Obese Youth Across the Spectrum of Glucose Tolerance From Normal to Prediabetes to Type 2 Diabetes

Abstract: OBJECTIVETo 1) determine if plasma 25-hydroxyvitamin D (25[OH]D) concentrations differ among obese youth with normal glucose tolerance (NGT) versus prediabetes versus type 2 diabetes and 2) assess the relationships between 25(OH)D and in vivo insulin sensitivity and β-cell function in this cohort.RESEARCH DESIGN AND METHODSPlasma 25(OH)D concentrations were examined in banked specimens in 9- to 20-year-old obese youth (n = 175; male 42.3%, black 46.3%) (NGT, n = 105; impaired glucose tolerance [IGT], n = 43; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
44
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 29 publications
1
44
1
Order By: Relevance
“…In recent years, the relationship between vitamin D and glucose metabolism has been widely analyzed, although the results have been conflicting (4,6,8,25,26). In this study, we observed that vitamin D status and HOMA SDS differed between obese subjects during prepuberty and puberty.…”
Section: Discussionmentioning
confidence: 59%
“…In recent years, the relationship between vitamin D and glucose metabolism has been widely analyzed, although the results have been conflicting (4,6,8,25,26). In this study, we observed that vitamin D status and HOMA SDS differed between obese subjects during prepuberty and puberty.…”
Section: Discussionmentioning
confidence: 59%
“…Although lower 25-OH-D has been associated with incident T2DM (7)(8)(9)43) and decline in b-cell function over time (10,11) in several observational studies, other investigators have noted conflicting results (13,15,16,18). In addition, interventional studies aiming to evaluate the effect of vitamin D supplementation on glucose metabolism have yielded inconsistent conclusions (19)(20)(21)44,45).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have also reported that increased PTH is associated with insulin resistance (12) and metabolic syndrome (4,13), and deterioration of insulin sensitivity and b-cell function has been described in hyperparathyroid states (14). Conversely, however, many investigators have questioned the association of vitamin D and PTH with glucose metabolism, particularly in light of several observational studies (13,(15)(16)(17)(18) and interventional trials (1,(19)(20)(21) that either have been negative or showed only modest beneficial effects of vitamin D supplementation on glucose homeostasis.…”
mentioning
confidence: 99%
“…16 However, in a recent study on 175 obese adolescents, of whom 60% were euglycemic, 25% prediabetic and 15% diabetic, Las Heras et al did not find any difference in serum 25OHD3 between these groups, or any association with any metabolic parameters, even though the prevalence of low levels of vitamin D was higher in both groups. 27 Another study, on 150 obese children and adolescents living in the tropics, found vitamin D levels ≥ 20 ng/ml in 88.6%, with no difference in the prevalence of prediabetes in relation to the group with levels lower than 20 ng/ml. 28 In spite of our negative results regarding the correlation between prediabetes and vitamin D, measurement of 25OHD3 levels in patients with prediabetes is important because of the worldwide problem of vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 99%